The Numerical Phenetic of Taxonomy Vibrio in Shellfish (Meretrix meretrix) at Edu-Tourism Mangrove Cengkrong Beach Trenggalek - Burhanuddin Ihsan; Endah Retnaningrum (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
Highlight • Identify the Vibrio bacteria • Diversity of shellfish Vibrio bacteria (Meretrix Meretrix) • Relationship similarity of Vibrio bacteria with MVSP 3.1 Program produces Dendogram